Exploiting resource heterogeneity in delay‐tolerant networks1. Issue 3 (31st January 2012) - Sandulescu, Gabriel; Schaffer, Péter; Nadjm‐Tehrani, Simin; Gerla, Mario; Maggiorini, Dario; Palazzi, Claudio E.
ABSTRACT Routing in delay and disruption‐tolerant networks (DTNs) relies on intermediary nodes, called custodians, to deliver messages to destination. However, nodes usually differ significantly in terms of available resources: energy, buffer space and bandwidth. Routing algorithms need to make the most efficient use of custodian resources while also making sure those in limited supply are not exhausted. This paper proposes a distributed scheme for calculating resources available in node vicinity as a tool to support meaningful routing decisions. A generic model is developed first and is then applied to individual network assets. The model is based on a sparse network, where resources are potentially not uniformly distributed. It uses recent encounters to estimate resource availability in node vicinity. It is shown that a store‐carry‐forward scheme may benefit from accessing vicinity resource estimates. This knowledge allows nodes to implement meaningful custodian election and queue management strategies, approached here from a holistic perspective. It is demonstrated that routing protocols not only use up fewer resources overall but also consume resources preferentially from nodes with higher resource levels, sparing nodes with limited supplies. As a result, disparities in available resources across the node population are significantly reduced, and nodes are less likely to leave the network as a consequence of resource depletion. Copyright © 2012 John Wiley & Sons, Ltd.